Clinical Implications of Nutritional Consultations and Oral Nutritional Supplementation Refusal in Head and Neck Cancer Patients During Chemoradiotherapy - Aleksandra Krzywon; Anna Kotylak; Jolanta Mrochem-Kwarciak; Tomasz Rutkowski (Nutrients, 2026)
Background/Objectives: Nutritional support may improve the tolerance and effectiveness of definitive treatment in patients with head and neck cancer (HNC). The aim of this study was to investigate the potential clinical deterioration in patients who refuse nutritional consultations and oral nutritional supplementation during chemoradiotherapy (CHRT) for HNC. Methods: The study included 52 patients undergoing CHRT for HNC. Among these patients, 22 (42.3%) received nutritional counseling with oral nutritional supplementation (NCONS), while 30 (57.7%) patients refused NCONS (R-NCONS). The study aimed to investigate and compare the association of NCONS with weight loss, blood parameters, CHRT complications, and overall survival (OS) between the two groups. Results: At the end of CHRT, the R-NCONS group exhibited significantly higher CRP levels (18 mg/L vs. 4 mg/L; p = 0.013) and lower prealbumin levels (0.19 g/L vs. 0.27 g/L; p = 0.003) compared with NCONS group. Furthermore, R-NCONS patients experienced a higher rate of overall complications during CHRT (67% vs. 32%; p = 0.013), required enteral nutrition more frequently (20% vs. 0%; p = 0.033), and exhibited greater weight loss (−11% vs. −5%; p < 0.001). However, the 5-year OS did not differ significantly between the groups. Conclusions: The study demonstrates that while NCONS minimizes overall complications during CHRT, its refusal results in weight loss, elevated CRP and depleted prealbumin levels, and a more frequent need for enteral nutrition interventions.